1982
DOI: 10.1210/jcem-55-1-181
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Secretion by Granulosa Cells from Different Sized Follicles of Human Ovaries after Short Term Incubation*

Abstract: Studies on the ability of granulosa to secrete progesterone after hormonal treatment have not addressed the possibility of variations in response associated with the stage of follicular development. Accordingly, granulosa were isolated from follicular fluid obtained from apparently healthy ovaries of patients undergoing tubal bypass. Follicle size was estimated by laparoscopic and ultrasonic measurements, and granulosa cells were prepared by centrifugation and treatment with EGTA and hypertonic sucrose solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
1

Year Published

1984
1984
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
2
3
1
Order By: Relevance
“…The apparent discrepancy between our present findings and those of Bieszczad et al (1982) concerning the progesterone responsiveness of cells from small compared to large preovulatory follicles may actually be a function of the length of stimulation in vitro. In the 24-h incubation studies (Bieszczad et al, 1982), only granulosa cells from follicles <20 mm responded to ovine LH (1 µg/ml) with enhanced progesterone production, and the authors suggested that the inability of LH to affect progesterone secretion by cells from larger follicles might be due to a maximal binding of LH to the receptors at the time of culture or to desensitization. Our studies of 15-25-mm follicles tend to support the former hypothesis during the first 2 days of culture, but are not consistent with a continued down regulation.…”
Section: Discussioncontrasting
confidence: 99%
“…The apparent discrepancy between our present findings and those of Bieszczad et al (1982) concerning the progesterone responsiveness of cells from small compared to large preovulatory follicles may actually be a function of the length of stimulation in vitro. In the 24-h incubation studies (Bieszczad et al, 1982), only granulosa cells from follicles <20 mm responded to ovine LH (1 µg/ml) with enhanced progesterone production, and the authors suggested that the inability of LH to affect progesterone secretion by cells from larger follicles might be due to a maximal binding of LH to the receptors at the time of culture or to desensitization. Our studies of 15-25-mm follicles tend to support the former hypothesis during the first 2 days of culture, but are not consistent with a continued down regulation.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results indicate that oestradiol affects luteal progesterone biosynthesis directly and acutely by inhibiting the activities of 3B-HSD/AS-4-isomerase, the enzyme that catalyses oxidation of pregnenolone to progesterone. This is in accord with evidence that oestrogen inhibits the 3/3-HSD/ isomcrase system in microsomes of human placenta and CL of pregnancy (Depp et al, 1973) and in cultured human granulosa cells (Bieszczad et al, 1982;Veldhuis et al, 1983). Oestradiol action at this site is also consistent with earlier work suggesting that oestradiol exerts its inhibitory effect at a step(s) beyond the accumulation of CAMP (Williams et al, 1979).…”
Section: Discussionsupporting
confidence: 91%
“…The possibility that oestradiol is a locally produced luteolysin is supported by the finding that oestradiol inhibits progesterone accumulation by granulosa-lutein cells in uitro (Bieszczad et al, 1982). It has been suggested that the direct inhibitory effect of oestradiol on luteal cell steroidogenesis could involve inhibition of the 3/3-hydroxysteroid dehydrogenase (3P-HSD) enzyme system (Depp et al, 1973) or a reduction in the LH binding capacity of luteal cells (Sotrel et al, 1981).…”
mentioning
confidence: 99%
“…Also, granulosa cells morphologically differentiate from autosynthetic cells into steroid-secreting cells around the time of the LH surge (Wada et al 1986), and the amount of gonadotropin receptors increases markedly along with this change (Richards and Midgley 1976). Variations in the reaction of granulosa cells to steroid according to the maturity of the sampled cells have also been reported by Jarrell and Belbeck (1985) and Bieszczad et al (1982).…”
Section: Discussionmentioning
confidence: 99%